The Orphan Generation - Strategies for Hope (Small World Productions, 2015)
A film about community-based care and support for children orphaned by HIV and AIDS. How community-based organisations, rather than institutional care, are the key to meeting the urgent needs and protecting the rights of children affected or orphaned by AIDS. Produced by Small World Productions for Strategies for Hope.
Free